A Standard Modulo Priestley Topological Quasi-Variety - Begum, SN; Rahman, MR (GANIT: Journal of Bangladesh Mathematical Society, 2011)
We construct a topological quasi-variety which is not standard but standard modulo Priestley. Key words: Standard topological quasi-variety; Boolean model; standard modulo Priestley. GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 29 (2009) 35-41 DOI: http://dx.doi.org/10.3329/ganit.v29i0.8513